Interface between indigenous health and natural sciences: use of medicinal plants in indigenous education as a tool for sociocultural integration (Research, Society and Development, 2022)
Ethnoscience has been a priority aspect in the constitution of a stronger and more inclusive indigenous education, where, sometimes, aspects of the Amazonian flora are worked on in the classroom in order to bring students closer to their own culture. This article aims to carry out a narrative review of the literature on the use of medicinal plants in the basic education of indigenous peoples, correlating this methodology with the possible influences that this educational practice can have on the health of these peoples. For this, a search for studies was carried out in the Google Scholar and SciELO databases using the descriptors “medicinal plants”, “indigenous health”, “disciplines of the natural sciences” and “basic education”. We included 17 articles in Portuguese, published in the last 05 years and related to the theme proposed here. It was observed that the inclusion of elements of traditional medicine in the indigenous school context can be an effective way of cultural appreciation in the classroom, in addition to being a resource capable of re-signifying traditional health knowledge propagated over generations.